Enhancing Authentic Assessment Through Pedagogical Competence: Insights from Indonesian Language Teachers in Riau - Adristi Afdal; Desi Sukenti (STAI Hubbulwathan Duri, 2024)
This study examines the relationship between authentic assessment and pedagogical competence, which encompasses key indicators of the learning process, including planning, implementation, assessment, and evaluation. Mastery of pedagogical competence by teachers enhances the objectivity and quality of authentic assessment. A descriptive quantitative approach using a simple linear correlation method was employed. The study sampled 98 Indonesian language high school teachers in Riau Province. Data collection involved a research questionnaire designed to measure both authentic assessment practices and teachers' pedagogical competence. Analysis was conducted using SPSS software. The findings revealed that pedagogical competence positively influences authentic assessment, with an effect size of 75.2%. This indicates that higher levels of pedagogical competence correlate with improved ease and effectiveness in conducting authentic assessments. Teachers with well-developed pedagogical skills are more likely to achieve optimal outcomes in their assessment practices. The results underscore the critical role of pedagogical competence in facilitating meaningful and objective authentic assessments. This relationship highlights the need for teacher professional development programs that emphasize pedagogical skills to enhance assessment quality. Pedagogical competence significantly impacts the effectiveness of authentic assessment, with stronger competence resulting in better outcomes. This study emphasizes the importance of prioritizing teacher training in pedagogical areas to advance authentic assessment practices, thereby enriching the learning experience for students.